Dislipidemia sebagai Faktor Risiko Penurunan Nilai Estimasi Laju Filtrasi Glomerulus (eLFG) pada Diabetes Mellitus Tipe II - DITA MARIA VIRGINIA; FENTY FENTY (Fakultas Farmasi Universitas Pancasila, 2015)
Prevalence of diabetes mellitus type II is high in the world as well as in Indonesia which is 55% patient get dyslipidemia. The risk of cardiovascular disease arises on patient DM type 2 with dyslipidemia so that it is possible to make vasoconstriction in renal artery getting worse. Renal function value can mark from estimated glomerular filtration rate (eGFR). The aim of this study is to determine dyslipidemia in DM type II as risk factor on declining renal function which is marked from decreasing eGFR. This study was analytical observational with cross sectional design. This study compared eGFR between DM type II patient with and without dyslipidemia in Hospital X, Central Java, Indonesia. A hundred subject participated in this study. Data have analyzed in descriptive and Chi-Square using SPSS. Result showed Dyslipidemia on patient Diabetes Mellitus (DM) type II was not risk factor for declining renal function based on eGFR value (OR=0,711, CI95%= 0,270 – 1,875).